What works for GE may not work for you : using human systems dynamics to build a culture of process improvement - Solow, Lawrence (Lawrence A.) (Productivity Press, 2010)
Offers tools for managing and sustaining process improvement in the complex non-linear environments, and helps readers apply relevant theory to their own management practices. This title offers practical insights for creating dynamic organizational change. It describes the key bodies of knowledge and process improvement processes.